Teaching English Pronunciation Using Songs and Tongue Twister - Putu Edina Prassista Rasmadiani (STKIP AGAMA HINDU SINGARAJA, 2023)
The study aimed to compare two distinct methods of teaching English pronunciation using songs and tongue twister. The library study method was used in this study to gather the information for this research. As the result of the research, it was showing that using songs to teach English pronunciation can help students mimic the native speakers’ pronunciation while also increasing students’ interest and engagement in learning English, resulting in a good learning environment. Using songs can be a relaxing and fun way to learn English. Students can also be more expressive when practicing speaking English and learning English pronunciation. Besides using songs, there is also another engaging way to teach and learn English pronunciation, which is by using tongue twister. Tongue twister known as the most challenging game in speaking languages, especially in English. Using tongue twister in teaching English pronunciation, can be a fun learning activities in the classroom because students are challenged to speak as fast as possible, and with a clear pronunciation as possible.